Improved Physical Health of Children During The Covid-19 Pandemic in Banjarmasin - Suci Fitri Rahayu (UMBanjarmasin, 2021)
Malnutrition or severe wasting is the most dangerous malnutrition problem, because it increases the risk of child mortality up to 12 times. Children who suffer from malnutrition also experience a higher risk of becoming stunted and also in the long term will affect growth, brain development and also the ability to earn a living as an adult. The COVID-19 pandemic is expected to significantly increase the risk of children experiencing malnutrition and potentially worsen the existing conditions given that various access to health services, access to food and interventions that can be done to improve the nutritional health of children in Indonesia are hampered. Child development services are very important because developmental disorders detected early will receive appropriate interventions. The main activities to monitor children's growth and development have stopped being implemented in health services or schools. From the results of observations in the Banjarmasin City Region, it was found that activities in monitoring children's growth and development were less than optimal during the COVID-19 pandemic. The purpose of this community service activity is to improve physical health during the COVID-19 pandemic by physical examination of children and providing additional nutrition at school. The method starts from a physical examination and providing additional nutrition at school. The activity was carried out in August 2021. The activity was carried out at the Banjarmasin City Regional Elementary School. This activity was attended by 32 children. The implementation of the activities went well and smoothly. This activity raised a theme